Localisation of the e-Educator module: the Malaysian experience - Thang, Siew Ming; Joyes, Gordon (Anadolu University, Eskisehir, 2009)
The University of Nottingham, UK and Beijing Foreign Studies University, China developed a module for training tutors of online learners - one that could be adapted for use in a variety of contexts. The module was piloted at the School of Distance Education, Universiti Sains Malaysia, Penang with eight staff members (six tutors and two local mentors). They undertook to work through the different units of the e-Educator module and complete all the e-Educator tasks required which include online forums and other online activities. They were also required to complete reflective blog entries at regular intervals. This paper will share the results of the four focus group interviews and the reflections of one of the tutors. The findings of the focus groups were analysed first and then triangulated with the reflections of the tutor to give a more holistic picture of the Malaysian experience. The findings revealed that the e-Educator module curriculum was perceived as highly relevant to the tutors and impacted on their personal and professional development, establishing a community of practice for the tutors involved. However, the extent to which it can be localised needs to be explored further.